Active volcanism on Venus in the Ganiki Chasma rift zone. Issue 12 (17th June 2015) - Shalygin, E. V.; Markiewicz, W. J.; Basilevsky, A. T.; Titov, D. V.; Ignatiev, N. I.; Head, J. W.
Abstract Venus is known to have been volcanically resurfaced in the last third of solar system history and to have undergone a significant decrease in volcanic activity a few hundred million years ago. However, fundamental questions remain: Is Venus still volcanically active today, and if so, where and in what geological and geodynamic environment? Here we show evidence from the Venus Express Venus Monitoring Camera for transient bright spots that are consistent with the extrusion of lava flows that locally cause significantly elevated surface temperatures. The very strong spatial correlation of the transient bright spots with the extremely young Ganiki Chasma, their similarity to locations of rift‐associated volcanism on Earth, provide strong evidence for their volcanic origin and suggests that Venus is currently geodynamically active.